Antibodies to Influenza Virus A/H1N1 Hemagglutinin in Type 1 Diabetes Children Diagnosed Before, During and After the SWEDISH A(H1N1)pdm09 Vaccination Campaign 2009–2010. (February 2014) - Svensson, M.; Ramelius, A.; Nilsson, A.‐L.; Delli, A. J.; Elding Larsson, H.; Carlsson, A.; Forsander, G.; Ivarsson, S. A.; Ludvigsson, J.; Kockum, I.; Marcus, C.; Samuelsson, U.; et al.
Abstract We determined A/H1N1‐hemagglutinin (HA) antibodies in relation to HLA‐DQ genotypes and islet autoantibodies at clinical diagnosis in 1141 incident 0.7‐to 18‐year‐old type 1 diabetes patients diagnosed April 2009–December 2010. Antibodies to 35S‐methionine‐labelled A/H1N1 hemagglutinin were determined in a radiobinding assay in patients diagnosed before (n = 325), during (n = 355) and after (n = 461) the October 2009–March 2010 Swedish A(H1N1)pdm09 vaccination campaign, along with HLA‐DQ genotypes and autoantibodies against GAD, insulin, IA‐2 and ZnT8 transporter. Before vaccination, 0.6% patients had A/H1N1‐HA antibodies compared with 40% during and 27% after vaccination (P < 0.0001). In children <3 years of age, A/H1N1‐HA antibodies were found only during vaccination. The frequency of A/H1N1‐HA antibodies during vaccination decreased after vaccination among the 3 < 6 (P = 0.006) and 13 < 18 (P = 0.001), but not among the 6 < 13‐year‐olds. HLA‐DQ2/8 positive children <3 years decreased from 54% (15/28) before and 68% (19/28) during, to 30% (9/30) after vaccination (P = 0.014). Regardless of age, DQ2/2; 2/X (n = 177) patients had lower frequency (P = 0.020) and levels (P = 0.042) of A/H1N1‐HA antibodies compared with non‐DQ2/2; 2/X (n = 964) patients. GADA frequency was 50% before, 60% during and 51% after vaccination (P = 0.009). ZnT8QA frequency increased from 30% before to 34% during and 41% after vaccination (P = 0.002). Our findings suggest that young (<3 years) along with DQ2/2; 2/X patients were low responders to Pandemrix®. As the proportion of DQ2/8 patients <3 years of age decreased after vaccination and the frequencies of GADA and ZnT8QA were enhanced, it cannot be excluded that the vaccine affected clinical onset of type 1 diabetes.